Filles déscolarisées et apprentissage des « métiers masculins » dans la ville de Kinshasa : quelle image sociale ? - Alokpo, Dieudonné Musa (Afrika Focus, 2015)
In the city of Kinshasa there has been a marked increase in the numbers of women expressing an interest in jobs traditionally thought of as male occupations. The case of the out-of-school girls learning mechanics is a good illustration of this new phenomenon. In a society in which access to employment in the formal sector is saturated, apprenticeships organized in non-formal educa- tional centers offer out-of-school girls the opportunity to develop practical skills that can be used immediately, and so help them create their own employment opportunities. The choice to learn the 'male occupation' of mechanics contrasts with the cultural conceptions about the boundaries between the female and male oriented work. Considering such a contrast, and the recurring politi- cal discourse concerning gender equality, which encourages women to integrate into all spheres of social activity, it is interesting to question the inhabitants of Kinshasa about the relevance of the occupation choices of the out-of-school girls and about their skill levels in the "male jobs" arena. The survey showed that the inhabitants of Kinshasa are against the division of work along gender lines and remain in favor of the idea that men and women should be able to pursue jobs according to their skills rather than their sex.